Delik Culpa dalam Kajian Fiqh Jinayah (Analisis terhadap Pasal 359 KUHP tentang Kealpaan yang Mengakibatkan Matinya Orang) - Seva Maya Sari; Toguan Rambe (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2020)
Errors in criminal law studies are known in two forms, namely errors based on the element of intent (dolus) and errors based on the element of starvation (culpa). Negligence (Culpa offense) which the perpetrator did not want. Cases related to Delik Culpa where a person, due to his negligence, committed a criminal act, was often committed by the community. This case is not uncommon and there are still pros and cons in the field of law. There are many examples of cases where due to their negligence other people died. As the explanation of article 359 of the Criminal Code in the positive criminal law for the criminal offender (offense Culpa), even though his negligence has taken the life of another person, he is still convicted. It is known that the Islamic Criminal Law (Fiqh Jinayah), there is a classification of criminal acts and sanctions, negligence in murder (fi qatli al khata ') is someone who commits an act accidentally, but by reason of this action it can result in the loss of another person's life. The penalty for errant murder is almost the same as for deliberate murder, namely the basic punishment of diyat and kafarat, and the substitute punishment is ta'zir and fasting and there are additional penalties, namely deprivation of inheritance rights and revocation of the right to receive a will